Architectural shop drawing of CC3 & CC5 demarcation layout of roof storey (RFA-413_Rev B) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.